Predictors for postoperative dysphagia in liver transplant recipients - Isdahl, Marian; Katz, Lily; Johnson, Michaela; Leverson, Glen; Al-Adra, David; Thibeault, Susan (Frontiers in Transplantation, 2024)
IntroductionLiver transplant recipients are at a heightened risk for oropharyngeal dysphagia; identification of those who are at high risk for postoperative dysphagia could reduce hospital costs and length of stay. We sought to identify predictors of dysphagia, in a large cohort of patients who underwent liver transplantation.MethodsElectronic medical records were queried for patients undergoing liver transplantation, who underwent instrumental swallowing evaluations. Demographics, functional outcomes, and interventions were collected. Logistic regression analyses were performed to identify predictors of dysphagia.ResultsSeven hundred and ninety-five patients met inclusionary criteria. Multivariate analyses found ethnic group (p = .0191), MELD Score (p < 0001), cold ischemia time (p = .0123), and length of intubation (p < .0001) to be predictors of post-operative development of dysphagia. Pre-transplant dialysis (p < .0001), dysphagia related to end stage liver disease (p < .0001), Karnofsky Performance Status Scale (p < .0001), wait time to transplant (p = 0.0173), surgery time (p = 0.0095), tracheostomy (p < 0.0001), and transfusion of intraoperative RBC (p < .0001), intraoperative platelets (p = 0.0018), intraoperative FFP (p = 0.0495), perioperative FFP (p = 0.0002), perioperative platelets (p = 0.0151) and perioperative RBC (p = 0.0002) were variables of significance associated with the development of postoperative dysphagia from univariate analysis.ConclusionsOur results propose a set of predictors that should be considered when identifying post-operative critically ill patients at risk for dysphagia.